Negative effects of the SARS-CoV-2 pandemic: The interlinking of maternal attachment representation, coping strategies, parental behavior, and the child's mental health - Gulde, Manuela; Köhler-Dauner, Franziska; Mayer, Inka; Ziegenhain, Ute; Fegert, Jörg M.; Buchheim, Anna (Frontiers in Pediatrics, 2022)
Background For more than two years, young families have been confronted with a large number of restrictions and burdens as a result of the SARS-CoV-2 pandemic. In fact, it became evident, that the current circumstances are particularly stressful for child's psychosocial health. With regard to the child's psychosocial health in times of a pandemic, additional risk factors within the family, such as parental attachment representations as well as coping strategies and parental behavior, may play an important role. Objective This study aims to investigate the interplay of maternal attachment representation, coping strategies, parental behavior and child's psychosocial health during the SARS-CoV-2 pandemic. Method In this longitudinal study, previously collected data regarding maternal attachment representation were combined with data regarding lack of coping strategies, children´s mental health (behavioral, emotional, and hyperactivity), and parenting quality during the SARS-CoV-2-pandemic were analyzed. The data since beginning of the pandemic were collected in an online survey, including N=73 mothers. A path model was calculated in form of multiple linear regression. Results A path model could be confirmed, with following order of variables: maternal attachment representation, lack of coping strategies, parenting quality, and mental health problems, especially behavioral problems, of their child. As control variables presence of short-time work, and decrease in income since beginning of the pandemic. Conclusions Behavioral problems in children are especially influenced by the parenting style, whereas emotional problems in children are mainly influenced by excessive demands of their caregiver. Therefore, tailored interventions for different kinds of mental peculiarities in children should be offered. Moreover, insecure attachment and a lack of coping strategies may additionally contribute to explain the vicious cycle of violence to the next generation, especially in times of a pandemic.